2016
DOI: 10.5194/hess-20-755-2016
|View full text |Cite
|
Sign up to set email alerts
|

Variability in snow cover phenology in China from 1952 to 2010

Abstract: Abstract. Daily snow observation data from 672 stations in China, particularly the 296 stations with over 10 mean snow cover days (SCDs) in a year during the period of 1952-2010, are used in this study. We first examine spatiotemporal variations and trends of SCDs, snow cover onset date (SCOD), and snow cover end date (SCED). We then investigate the relationships of SCDs with number of days with temperature below 0 • C (TBZD), mean air temperature (MAT), and Arctic Oscillation (AO) index. The results indicate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…Our study showed that over the past 14 years, the SCDs and SD decreased primarily in the hinterlands of the Tibetan Plateau, and increased in the southwest and southeast margins of the Tibetan Plateau. Studies based on long time series of observations by ground stations have indicated that the number of SCDs and the SD in northeast China increased every year (Chen and Li, 2011;Yan et al, 2015;Ke et al, 2016), which is consistent with our results for northeast China over the past 14 years.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that over the past 14 years, the SCDs and SD decreased primarily in the hinterlands of the Tibetan Plateau, and increased in the southwest and southeast margins of the Tibetan Plateau. Studies based on long time series of observations by ground stations have indicated that the number of SCDs and the SD in northeast China increased every year (Chen and Li, 2011;Yan et al, 2015;Ke et al, 2016), which is consistent with our results for northeast China over the past 14 years.…”
Section: Discussionsupporting
confidence: 91%
“…This result is similar to the results obtained by Huang et al (2017), who used MODIS daily snow cover products from 2001 to 2014. Ke et al (2016) found 370 that from 1952 to 2010, the overall snow phenology in China showed a delay in the SOD and advancement of the SED. This result is similar to the results of our study.…”
Section: Discussionmentioning
confidence: 98%
“…China's annual mean snow covered area accounts for 27% of the country's total area in the winter (Huang et al, 2016). Ke et al (2016) found that a delayed snow onset date (SOD) and 60 advanced snow end date (SED) are common in China during the period of 1952 to 2010. There are three snow cover areas in China: Northeast China, northern Xinjiang and the Tibetan Plateau (Liu et al, 2014).…”
mentioning
confidence: 99%
“…(2) Onset date of snow cover accumulation (SCOD): the start dates (Julian day) of the stable snow cover duration in a hydrological year [49,50]. It is defined as the first day when snow cover is initially observed to exist for at least five consecutive days; (3) End date of snow cover (SCED): the ending date (Julian day) of the snow cover.…”
Section: The Relationship Between Winter Snow Cover Climate and Vegmentioning
confidence: 99%